Prospective Analyses of Sedentary Behavior in Relation to Risk of Ovarian Cancer. Issue 6 (28th January 2022) - Buras, Andrea L; Wang, Tianyi; Whiting, Junmin; Townsend, Mary K; Fridley, Brooke L; Tworoger, Shelley S
Abstract: We examined the association of sedentary behavior with risk of ovarian cancer overall, by tumor subtype, and by participant characteristics in the Nurses' Health Study (NHS) and Nurses' Health Study II (NHS II). A total of 69, 558 NHS participants (1992–2016) and 104, 130 NHS II participants (1991–2015) who reported on time spent sitting at home, at work, and while watching television were included in the analysis, which included 884 histologically confirmed ovarian cancer cases. Multivariable-adjusted Cox proportional hazards models were used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) for ovarian cancer by sitting time (no mutual adjustment for individual sitting types in primary analyses). We examined potential heterogeneity by tumor histological type (type I or II), body mass index (weight (kg)/height (m) 2 ; < 25 or ≥25), and total physical activity (<15 or ≥15 metabolic equivalent of task–hours/week). We observed an increased risk of ovarian cancer for women who sat at work for 10–19 hours/week (HR = 1.25, 95% CI: 1.04, 1.51) and ≥20 hours/week (HR = 1.40, 95% CI: 1.14, 1.71) versus <5 hours/week. This association did not vary by body mass index, physical activity, or histotype ( P for heterogeneity ≥ 0.43). No associations were observed for overall sitting, sitting while watching television, or other sitting at home. Longer sitting time at work was associated with elevated risk of ovarian cancer. Further investigations are required to confirm these findings and elucidate underlying mechanisms.